The impacts of quality improvement on maternal and newborn health: preliminary findings from a health system integrated intervention in four Ethiopian regions - Ashley K. Hagaman; Kavita Singh; Mehiret Abate; Haregeweyni Alemu; Abera Biadgo Kefale; Befikadu Bitewulign; Abiy Seifu Estifanos; Abiyou Kiflie; Zewdie Mulissa; Hillina Tiyo; Yakob Seman; Meseret Zelalem Tadesse; et al. (BMC Health Services Research, 2020)
Abstract Background Quality improvement (QI) methods are effective in improving healthcare delivery using sustainable, collaborative, and cost-effective approaches. Systems-integrated interventions offer promise in terms of producing sustainable impacts on service quality and coverage, but can also improve important data quality and information systems at scale. Methods This study assesses the preliminary impacts of a first phase, quasi-experimental, QI health systems intervention on maternal and neonatal health outcomes in four pilot districts in Ethiopia. The intervention identified, trained, and coached QI teams to develop and test change ideas to improve service delivery. We use an interrupted time-series approach to evaluate intervention effects over 32-months. Facility-level outcome indicators included: proportion of mothers receiving four antenatal care visits, skilled delivery, syphilis testing, early postnatal care, proportion of low birth weight infants, and measures of quality delivery of childbirth services. Results Following the QI health systems intervention, we found a significant increase in the rate of syphilis testing (ß = 2.41, 95% CI = 0.09,4.73). There were also large positive impacts on health worker adherence to safe child birth practices just after birth (ß = 8.22, 95% CI = 5.15, 11.29). However, there were limited detectable impacts on other facility-usage indicators. Findings indicate early promise of systems-integrated QI on the delivery of maternal health services, and increased some service coverage. Conclusions This study preliminarily demonstrates the feasibility of complex, low-cost, health-worker driven improvement interventions that can be adapted in similar settings around the world, though extended follow up time may be required to detect impacts on service coverage. Policy makers and health system workers should carefully consider what these findings mean for scaling QI approaches in Ethiopia and other similar settings.